Lycopene supplementation regulates the gene expression profile and fat metabolism of breeding hens. Issue 3 (13th March 2020) - Tian, Hanchen; Liu, Guangbin; Guo, Yongqing; Li, Yaokun; Deng, Ming; Liu, Dewu; Sun, Baoli
Abstract: This study investigated the effects of lycopene on the gene expression profile and expression of genes related to fat metabolism of Xinghua breeding hens. Seven hundred and twenty healthy breeding hens were randomly assigned to four treatments; each treatment was replicated six times with 30 hens each. Broken rice and soybean meal were adopted for the basal diet and added with 0 (control group), 20, 40 and 80 mg/kg lycopene respectively. Gene expression profile of the liver induced by lycopene and expression of genes related to fat metabolism in hens liver and intestine were analysed after 42‐day feeding trial including 7‐day pre‐feeding period and 35‐day formal period. The genes involved in fat metabolism were analysed, and we found that lycopene significantly increased the expression of PGC1α, PPARα, RXRα and RARα in the liver, PPARγ, RXRα and RXRγ in the jejunum, and RARα in the duodenum ( p  < .05); reduced the expression of FABP1 and FABP10 in the liver, and FATP4 in the jejunum ( p  < .05). By analysing gene expression profile, 158 differentially expressed genes (DEGs) including 69 up‐regulated genes and 89 down‐regulated genes were obtained between control group and 40 mg/kg group. KEGG pathway analysis was performed on all DEGs, and 5 pathways were obtained. In conclusion, lycopene can affect the expression of related genes, and this may be one of the reasons that lycopene can regulate fat metabolism.